Comparative study of the immunomodulatory activities of lactobacilli strains in porcine intestinal epithelial cells: effect on the innate antiviral immune response - Albarracín, Leonardo Miguel (2018)
Lactobacillus rhamnosus CRL1505 and L. plantarum CRL1506 are immunomodulatory probiotic strains (immunobiotics) with the ability to improve the intestinal antiviral response and the protection against viral infections as demonstrated in animal models and clinical trials. In order to advance in the understanding of the mechanisms involved in the antiviral capacities of both immunobiotic strains, we have previously performed comparative transcriptomic studies in porcine intestinal epithelial (PIE cells). These cells were stimulated with L. rhamnosus CRL1505 or L. plantarum CRL1506 and then challenged with the TLR3 agonist poly(I:C). The immunotranscriptomic response of PIE cells was evaluated 12 h after TLR3 activation by poly(I:C) stimulation. Our results showed that both immunobiotic strains significantly improved the expression of IFN-α and IFN-β as well as the antiviral factors RNASE4, RNASEL, OAS1, OASL, MX1, and MX2 when compared to controls. In addition, both lactobacilli strains increased the expression of cytokines (IL-1β, IL-6), chemokines (CCL4, CCL20, CCL28, AMCF-II, CXCL10), and enzymes involved in prostaglandin biosynthesis (PTGES, PTGER4). For the majority of these genes, their expression in CRL1505-treated PIE cells was significantly higher than in cells treated with the CRL1506 strain. Furthermore, only L. rhamnosus CRL1505 differentially regulated the expression of CXCL2, CXCL5, and CXCL11. Then, our transcriptomic analysis successfully allowed us to identify a group of genes that can be used as prospective biomarkers for the screening of new antiviral immunobiotics in PIE cells (Albarracin et al, 2017, Front Immunol 8:57). The aim of this work was to evaluate whether the immunotranscriptomic changes induced by L. rhamnosus CRL1505 and L. plantarum CRL1506 in PIE cells are unique and not sheared by non-immunomodulatory strains of the same species.